CLINICAL AND MORPHOLOGICAL COMPARISON AT NEPHROPATHY IN PATIENTS WITH MICROSCOPIC POLYANGIITIS - O.V. Syniachenko; T.B. Bevzenko; O.O. Diadyk; M.V. Iermolaieva; E.D. Iegudina; D.V. Pomazan (Ukrainian Journal of Nephrology and Dialysis, 2015)
Introduction. Morphological signs of renal pathology in microscopic polyangiitis, their connection with extrarenal manifestations of the disease and urine laboratory parameters, as well as the pathogenesis of such nephropathy remain insufficiently studied, what became the purpose and objectives of this study.Material and methods. Nephrobiopsy was made 12 patients. The study was performed on microscope «OlumpusBX40», «Olumpus - C3030 - ADU», «Olympus DP - Soft», «Olympus - AX70», «Olympus - DP50».Results and discussion. Damage of glomeruli, stroma, tubules and vessels was detected without exception in all patients with deposition in the kidney structures of immunoglobulins A, G, M, C3and Clqcomponents of complement that depend on the presence ofcardiac, pulmonary, hepatic, articular and neurological pathologies, and morphological indicators of renal lesion affect the parameters of proteinuria, erythrocythuria, uricosuria, nitrituria and surface physicochemical properties of urine, associated with blood levels ofdifferent antibodies, rheumatoid factor and circulating of immune complexes.Conclusions. Renal involvement at microscopic polyangiitis affects all morphological structures and indicates the immunecomplex damage of glomeruli, stroma, tubules and vessels.